Structure–Electrochemical Performance Relationship in Rgo-Decorated Inverse Spinels Feco₂O₄ and Cofe₂O₄ for H₂O₂ Sensing - Brito-Ramírez, T (Elsevier Ltd, 2025)
Two inverse spinel-based nanocomposites, FeCo₂O₄/rGO (FCO/rGO) and CoFe₂O₄/rGO (CFO/rGO), were synthesized and evaluated as non-enzymatic hydrogen peroxide sensors. Mössbauer and XPS analyses revealed distinct cation distributions: FCO presented mixed Co²⁺/Co³ ⁺ valence and a higher proportion of Fe³ ⁺ in octahedral coordination compared to CFO. These structural differences governed the electrocatalytic behavior. Reduced graphene oxide enhanced charge transfer, leading to optimal sensitivities of 0.1368 μA μM⁻¹ (LOD = 0.037 μM) for FCoO/rGO at 0.200 V and 0.2281 μA μM⁻¹ (LOD = 0.118 μM) for CFO/rGO at 0.300 V. The Fe³ ⁺ occupancy in octahedral sites was identified as a key factor for catalytic efficiency. Both sensors exhibited excellent selectivity and successfully quantified H₂O₂ in real samples. These findings establish a direct correlation between cation distribution and electrochemical performance, providing insights for the rational design of ternary spinel/rGO electrocatalysts. © 2025 Elsevier B.V.